2012
DOI: 10.1097/aln.0b013e3182632341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Perioperative Oxygen Supplementation on 30-day Surgical Site Infection Rate in Abdominal, Gynecologic, and Breast Surgery

Abstract: Background: Benefits and limitations of supplementation with 80% fraction of inspired oxygen for preventing surgical site infections have not yet been clearly defined. Some studies have reported benefits in colorectal surgery, whereas trials in abdominal and gynecologic surgery have reported either no effect or a deleterious effect. Methods: Controlled, randomized, assessor-blind multicenter trial, the ISO 2 study, comparing the effects of hyperoxygenation (fraction of inspired oxygen, 80%) with those of 30% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 43 publications
0
50
0
9
Order By: Relevance
“…Nine studies (5,103 patients) reported on the incidence of SSI (table 1). 4 28 Seven studies used a standardized method for SSI assessment: three considered the ASEPSIS scoring system, 4,5,58 two used the definition of the Centers for Disease Control and Prevention, 30,63 and two considered a prospectively determined scoring system. 28,66 In all trials except one, 30 90-100% of patients received prophylactic antibiotics.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies (5,103 patients) reported on the incidence of SSI (table 1). 4 28 Seven studies used a standardized method for SSI assessment: three considered the ASEPSIS scoring system, 4,5,58 two used the definition of the Centers for Disease Control and Prevention, 30,63 and two considered a prospectively determined scoring system. 28,66 In all trials except one, 30 90-100% of patients received prophylactic antibiotics.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…[4][5][6][7][27][28][29][30][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Seven reports with additional data from 900 patients have not been considered for any previously published metaanalyses. [27][28][29][30]61,69,70 Two articles reporting on pulmonary outcomes 56 and PoNV, 7 respectively, were subgroup analyses of a multicenter study that reported on SSI. 5 Results of another multicenter study reporting on SSI and pulmonary outcomes 63 were reported in two further articles; one concentrated on pulmonary outcomes in obese patients 70 and the other on pulmonary outcomes in patients scheduled for laparotomy for ovarian cancer.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the true prevalence of SSI is underestimated, depending on surgical specialty, accepted and validated definitions and the comprehensiveness of postoperative surveillance [8][9] . When close post-discharge surveillance is included, particularly with the involvement of unbiased, trained and validated observers, SSIs have been reported to complicate 10-20% of surgical operations indicating that there is widespread underestimation of SSI rates across all classes of surgery [10][11][12][13][14][15][16][17][18] .…”
Section: Introduction Epidemiology and Costs Of Ssismentioning
confidence: 99%
“…On the other hand 7 trials including 2992 patients reported no benefit of 80% inspired oxygen (. Table 1) [2,12,13,15,20,26,28]. The WHO panel members based their recommendations on a meta-analysis of 11 randomized trials of supplemental oxygen during and after general anaesthesia.…”
Section: Adult Patients Undergoing General Anaesthesia With Endotrachmentioning
confidence: 99%